Police conduct toward complainants of crime: Cross-sectional study of Punjab Police - Zaheer Abbas; Muhammad Babar Akram; Muhammad Saud (Faculty of Social and Political Science, Universitas Airlangga, 2020)
The continual debate about the purpose, role, and function of the police for making the well-known organization is of keen interest for scholars. The present study aimed to explore the role of police conduct and its relationship with the complainants of crime in Pakistan’s geographical area. The study utilized a quantitative research design to gather data from the field. A research instrument prepared to collect the data from respondents who have ever interacted with the police. The sample size of 385 respondents selected for the known population and multistage and proportionate random sampling techniques were applied to draw the sample. The study was limited to Gujrat District in Punjab Province, and respondents selected through this universe. The study revealed significant barriers that restrict the police department’s efficiency and gain public trust in them. Theoretically, it was beneficial for elevating Pakistani criminology on the subject and practice; the research provides insights for taking the appropriate measures for better police-public liaison. The study’s findings revealed that the complainants generally agreed that they have limited trust in the police and that political interference is one of the major causes of lack of public trust.